2021
DOI: 10.3390/ijgi10050272
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Influence of Land Use/Land Cover Change Dynamics on Surface Urban Heat Island: A Case Study of Abuja Metropolis, Nigeria

Abstract: Rapid urbanization in cities and urban centers has recently contributed to notable land use/land cover (LULC) changes, affecting both the climate and environment. Therefore, this study seeks to analyze changes in LULC and its spatiotemporal influence on the surface urban heat islands (UHI) in Abuja metropolis, Nigeria. To achieve this, we employed Multi-temporal Landsat data to monitor the study area’s LULC pattern and land surface temperature (LST) over the last 29 years. The study then analyzed the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 82 publications
(144 reference statements)
3
25
0
Order By: Relevance
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
“…This result shows that the LST has increased with increases in the area of built-up and bare lands, while increasing the area of vegetation and water bodies has reduced the LST in the study area. These particular results is in line with previous research showing the significant effect of vegetation on the LST [37,[100][101][102][103][104][105][106][107][108][109][110]. In this regard, Rahman et al [97], by modeling the spatial changes in the coastal lands and their effects on the LST characteristics, showed that physical changes due to urban development and built-up lands have a direct and significant effect on the LST, and this could pose a challenge for the residents of the studied areas in the future.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Countries like India, China, and Nigeria will have an estimated urban population of approximately 416 million, 255 million, and 189 million, respectively [20]. This growth could increase land surface temperatures, leading to the development of Urban Heat Islands (UHI) in these geographical areas [21]. The emergence of urban heat islands that influence urban climate can be attributed to the transformation of land uses and the rapid urbanisation of cities [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The micro-climate of the Bangkok metropolitan region in Thailand was recently estimated relative to the city's future expansion [39]. The results showed that modification of the vegetated areas in the city's western region with low-rise and mid-rise buildings would increase the future surface temperature of the region by approximately 1 to 2 • C. Other studies conducted in Nigeria's cities of Abuja [21] and Potiskum [40], China's urban area of Shenzhen [41], Turkey's Sivas City [23], and five coastal cities in Pakistan [42] have demonstrated the relationship between LULC changes and LST using various satellite data and GIS techniques. However, comprehensive studies of cities in developing countries such as Nigeria are still limited.…”
Section: Introductionmentioning
confidence: 99%